Kampanye Gemar Makan Ikan (Gemarikan) dalam upaya Peningkatan Gizi di Kelurahan Pancor Kabupaten Lombok Timur - Dwiyanti, Septiana; Fitriani Mulyani, Laily; Asri, Yuliana (Program Studi Budidaya Perairan Universitas Mataram, 2023)
The low level of fish consumption in Indonesia has an impact on malnutrition. One of the efforts to improve nutrition from an early age is through the Fish-Eating Movement (Gemarikan) program. Gemarikan is a movement to motivate people to increase their fish consumption patterns. The importance of regulating fish consumption patterns from an early age must be prioritized because fish is one of the important sources of protein needed in the growth and development stages of children from an early age. The purpose of this community service is to be able to provide knowledge about the importance of consuming fish, so that they are more interested in consuming fish. fish compared to other foods. The service method consists of a location survey stage and the Gemarikan campaign through socialization. Participants in this service activity consist of early childhood with an age range of 6-12 years and the surrounding community. This activity was carried out at the Nurul Imam Al-Quran Education Park (TPQ) in the Pancor Lauq Mosque, East Lombok Regency. This activity received a very good reception as evidenced by the enthusiastic participants and lots of interaction in the form of discussion of participants and presenters during this activity. The benefits of this activity are expected to provide knowledge about the benefits of consuming it so that it can increase interest in consuming fish from an early age so that it can raise the degree of nutritional value for children in Indonesia, especially in East Lombok Regency.